2019
DOI: 10.1302/0301-620x.101b3.bjj-2018-1004.r1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in the elderly patient with a fracture of the odontoid process

Abstract: Aims Fracture of the odontoid process (OP) in the elderly is associated with mortality rates similar to those of hip fracture. The aim of this study was to identify variables that predict mortality in patients with a fracture of the OP, and to assess whether established hip fracture scoring systems such as the Nottingham Hip Fracture Score (NHFS) or Sernbo Score might also be used as predictors of mortality in these patients. Patients and Methods We conducted a retrospective review of patients aged 65 and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…1 Odontoid peg fractures have an overall mortality of 14.6% at 30 days and 34.1% at 1 year. 2 A separate study suggests that geriatric polytrauma has an overall mortality as high as 65%, with patients who suffer major blood loss (Hb <8 g/dL) having a mortality three times higher than those with moderate or minor blood loss (Hb ≥8 g/dL). 3 Cryoglobulinaemia accounts for nearly 25% of autoimmune haemolytic anaemia 4 and is important to rule out in cases of suspected haemolytic anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Odontoid peg fractures have an overall mortality of 14.6% at 30 days and 34.1% at 1 year. 2 A separate study suggests that geriatric polytrauma has an overall mortality as high as 65%, with patients who suffer major blood loss (Hb <8 g/dL) having a mortality three times higher than those with moderate or minor blood loss (Hb ≥8 g/dL). 3 Cryoglobulinaemia accounts for nearly 25% of autoimmune haemolytic anaemia 4 and is important to rule out in cases of suspected haemolytic anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies reported predictive and/or construct validity of eight scales (Table 4). The largest AUC and correlation coefficients of the reported predictive validity was 0.704 (moderate accuracy) [59] and 0.400 (medium strength) respectively [63], suggesting that all other scales were considered to have low accuracy and weak correlation regardless of domain of spinal disorders.…”
Section: Measurement Properties Of the Frailty Scalesmentioning
confidence: 99%
“…Approximately 59% of C2 fractures involve the odontoid process [3,4]. Mortality of C2 fractures in patients 65 years and older is substantial-approximately 15% at 30 days and 34% and 1 year [5]. The most common mechanism is motor vehicle accident, but in older patients even low energy trauma can result in odontoid process fractures [5].…”
Section: Craniocervical Junction (Ccj)mentioning
confidence: 99%
“…Mortality of C2 fractures in patients 65 years and older is substantial-approximately 15% at 30 days and 34% and 1 year [5]. The most common mechanism is motor vehicle accident, but in older patients even low energy trauma can result in odontoid process fractures [5]. There are three types of odontoid fractures as classified by Anderson and D'Alonzo (Fig.…”
Section: Craniocervical Junction (Ccj)mentioning
confidence: 99%